Influence of Agricultural Extension Role on Adoption of Durian Cultivation Innovation in Cepoko Mulyo Farmer Group - Zalfa Salsabila; Tutik Dalmiyatun; Joko Mariyono (Faculty of Animal and Agricultural Science, Diponegoro University, 2026)
Indonesia's agricultural sector faces challenges in low innovation adoption at the farmer level, particularly in the horticulture subsector. In Gunungpati District, Semarang City, the productive durian tree population declined drastically from 9,042 trees in 2022 to only 2,862 trees in 2024, indicating serious obstacles in the application of cultivation innovations. This study aimed to identify the socioeconomic characteristics of farmer group members, describe the form and intensity of agricultural extension agents' roles, analyze the level of durian cultivation innovation adoption, and analyze the influence of extension agents' roles on innovation adoption at Cepoko Mulyo Farmer Group in Gunungpati District, Semarang City. The study was conducted from January to May 2026 using a survey method with a census technique involving 37 active farmer group members as respondents. Primary data were collected through structured questionnaires that had been tested for validity and reliability (Cronbach's Alpha for variable X = 0.906; variable Y = 0.890), and analyzed using descriptive analysis and simple linear regression. Results showed that the majority of farmers were aged above 55 years (64.8%), had primary school education (67.6%), and managed sharecropping land of less than 2,000 m² (64.9%). The intensity of extension agents' roles was low, with 56.8% of respondents interacting only 0–1 time per year. The level of innovation adoption was in the moderate category (59.5%). Regression analysis produced the equation Y = 18.736 + 0.441X with a t-value of 3.014 (sig. 0.005 < 0.05), proving that the role of agricultural extension agents has a positive and significant effect on durian cultivation innovation adoption. The R² value of 0.206 indicates that the extension agents' role contributes 20.6%, while the remaining 79.4% is influenced by other factors such as free seedling assistance and the area's identity as a durian production center.